THE INFLUENCE OF LEARNING METHOD AND LEARNING MOTIVATION TOWARDS DISCUS THROW SKILLS OF SMP NEGERI 24 MAKASSAR - Suriah Hanafi (Journal of Innovation Research and Knowledge, 2023)
Discus throw is one of the main branches of athletic sport. Discus throw is included in sports learning material, including at SMP Negeri 24 Makassar, which is a place of research. Many learning methods are used in order to improve students' ability to master discus throwing skills, but in reality and practice in the field there are still many students who do not understand and are able to do what has been conveyed during learning. for that we need an appropriate learning method so that students can more easily master the skill of throwing discs. This research study, discusses the application of learning methods and student motivation in discus throwing skills.